Band K Satellite Receiver Signal and Radio Locator - Wnuk, Marian (Scientific Journal of Gdynia Maritime University, 2022)
The last dozen or so years has seen significant and dynamic development in satellite technologies. Devices using satellites circulating in space for the purposes of general communication have ceased to be the domain of a narrow group of recipients (mainly increased use by the military, governments and the media) and instead gained increasing numbers of new users. The paper presents a developed station for receiving satellite signals in the K band, with particular emphasis on the design and alignment of the antenna in the Cassegrain system.